Stakeholder - De Bussy, Nigel (Wiley, 2018)
Over the past three decades, the stakeholder concept has become one of the most ubiquitous themes in the field of management studies. The term is as commonplace in the world of commerce and industry as it is in the public sector. Stakeholders are frequently referred to by both practitioners and theorists of strategic communication. Yet the concept remains contentious and mired in definitional confusion. The contemporary stakeholder debate was sparked by an influential book published in the 1980s: R. Edward Freeman’s Strategic Management: A Stakeholder Approach (Freeman, 1984). Freeman remains today arguably the leading academic advocate for stakeholder theory, coauthoring a major review of the field in 2010 (Freeman, Harrison, Wicks, Parmar, & de Colle, 2010). Aside from the unresolved problems of who exactly is a stakeholder and precisely how stakeholders should be taken into account in management decision making, the relationship between the stakeholder concept and corporate social responsibility (CSR) remains a controversial issue. Arguably one of the greatest problems with the stakeholder concept is that it can mean different things to different people. For example Szwajkowski (2000) argued that even Milton Friedman is an adherent of the stakeholder concept (he applied similar logic to Adam Smith). Szwajkowski’s case was based on the qualification Friedman added to his famous profit maximization doctrine, namely that while pursuing profit (or shareholder wealth) managers must conform to the basic rules of society, both those embodied in the law and those embodied in ethical custom. Szwajkowski claimed the “ethical custom” caveat compels managers to consider broader societal concerns such as the competing interests of nonshareowner stakeholders. Yet the same argument could equally well deliver the opposite conclusion, that is, the “ethical custom” in much of the industrialized world is to maximize shareholder value in what is perceived to be the long-term interest of the economy as a whole.